Pengaruh Rekruitmen dan Stres Kerja Terhadap Kinerja Karyawan Pada Divisi Produksi PT Kenertec Power System di Kota Cilegon - Imam Kuryana; Taufik Hanafi; Tubagus Regiasa Regiasa (Prosiding Amal Insani Foundation, 2023)
This research aims to; (1) knowing the effect of employee recruitment on employee performance (2) knowing the effect of work stress on employee performance (3) knowing the effect of employee recruitment and work stress on employee performance. This research is a quantitative research that is used to examine certain populations or samples. Quantitative research applies the principles of objectivity, which are obtained, among others, through the use of instruments that have been tested for validity and reliability. Data analysis is quantitative/statistical in nature with the aim of testing the established hypothesis. The data analysis technique used is quantitative data, based on the results of data analysis it can be seen that (1) There is a significant effect of recruitment on employee performance at PT Kenertec Power System in Cilegon City with a significance level of <0.05 while a correlation value is obtained of 0.550, which means that the value of recruitment The more it increases, the employee's performance will increase as well. (2) There is a significant negative effect of work stress on employee performance (Y) at PT Kenertec Power System in Cilegon City with a significance level <0.05 while the correlation value is -0.578 in a negative direction, which means that the value of work stress decreases, employee performance will increase increase. (3) There is a significant effect of recruitment and work stress on employee performance at PT Kenertec Power System in Cilegon City while the coefficient of determination is 0.700. This means that the employee recruitment and work stress variables affect 70.0% of employee performance while the remaining 30.0% is influenced by other factors.